2003
DOI: 10.1093/nar/gkg336
|View full text |Cite
|
Sign up to set email alerts
|

Structural elements in the internal ribosome entry site of Plautia stali intestine virus responsible for binding with ribosomes

Abstract: Plautia stali intestine virus (PSIV) has an internal ribosome entry site (IRES) at the intergenic region of the genome. The PSIV IRES initiates translation with glutamine rather than the universal methionine. To analyze the mechanism of IRES-mediated initiation, binding of IRES RNA to salt-washed ribosomes in the absence of translation factors was studied. Among the three pseudoknots (PKs I, II and III) within the IRES, PK III was the most important for ribosome binding. Chemical footprint analyses showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
156
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(177 citation statements)
references
References 35 publications
10
156
0
Order By: Relevance
“…1D). Previous reports have implicated domains 1 and 2 as the parts of the IGR IRES primarily responsible for ribosome recruitment (14,17,18); our assays indicate that domain 3 by itself can bind to ribosomes, but at a much lower affinity than does the full-length IRES (∼2-10 nM) (18). Binding of the domain 3 RNA to 70S ribosomes was reduced by competitor tRNA, suggesting that the IRES domain occupies a tRNA binding site (Fig.…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…1D). Previous reports have implicated domains 1 and 2 as the parts of the IGR IRES primarily responsible for ribosome recruitment (14,17,18); our assays indicate that domain 3 by itself can bind to ribosomes, but at a much lower affinity than does the full-length IRES (∼2-10 nM) (18). Binding of the domain 3 RNA to 70S ribosomes was reduced by competitor tRNA, suggesting that the IRES domain occupies a tRNA binding site (Fig.…”
Section: Resultssupporting
confidence: 47%
“…Mutational analysis of IGR IRES RNAs has shown that the primary determinants for binding to the ribosome reside in domains 1 and 2; deletion of domain 3 has only a minor effect on ribosome binding affinity (17,42). In contrast, certain localized changes in domain 3 have profound effects on gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, structural studies performed on the HCV IRES and the IGR of members of the family Dicistroviridae have shown the capacity of these IRES elements to be accommodated in the interface of the ribosomal subunits (Spahn et al, 2001;Boehringer et al, 2005;Schuler et al, 2006;Pfingsten et al, 2006). Although the IGR and the HCV IRES elements exhibit different structural organization (Kieft et al, 2002;Rijnbrand et al, 2004;Jan & Sarnow, 2002;Nishiyama et al, 2003) and their binding sites in the ribosomal subunit are different, similar conformational changes are induced in the 40S ribosomal subunit (Spahn et al, 2004). This finding opens the possibility that IRES elements could share the property of having a universal structural IRES motif (USIM) that could mediate its direct interaction with the 40S subunit.…”
Section: Relevance Of Rna Structure For Ires Functionmentioning
confidence: 99%